Nonzero-Sum Time Perception Is Associated with Greater Willingness to Help - Yu Niiya; Syamil Yakin; Lora E. Park; Ya-Hui Chang (European Journal of Investigation in Health, Psychology and Education)
People are less likely to help others when they view time as a scarce resource. Does changing people’s perception of time influence their willingness to help? We hypothesized that people would be more willing to help and would allocate more time to helping others when they view time as a nonzero-sum resource (i.e., as a resource that merely exists or that can be created moment-by-moment with their interactions with others) versus a zero-sum resource (i.e., a commodity that can be lost, taken, or given away). Study 1 measured people’s perception of time and their willingness to help in hypothetical vignettes. Studies 2 and 3 manipulated the perception of time to examine its effect on people’s willingness to help others and the amount of time they wanted to spend helping. Study 3 further examined prosocial motivation as a potential mediator. Across the three studies, we demonstrated that when people perceive time as a nonzero-sum resource versus a zero-sum resource, people are more willing to help others. People’s prosocial motivation to reduce others’ distress mediated this relationship. We speculate that when people perceive time to be nonzero-sum, time spent helping others is not viewed as costly, but as a resource to invest in to benefit both themselves and others.